2D AND 3D QSAR USING MANUAL METHOD OF 6-BENZIMIDAZOLE DERIVATIVES, ZINC METALLOPEPTIDASE AS ACE INHIBITOR AS ANTI-HYPERTENSIVE AGENTS - K.RAJAMATHI,; M.KALIDASAN,; C. N. HEMALATHA,; M.VIJEY AANANDHI, (International Journal of Pharma and Bio Sciences, 2016)
Zinc metallopeptidase is a promising target for drug intervention and its inhibitors are useful in antihypertensive activity. QSAR (2D and 3D) studies were performed on a series of Benzimidazole derivatives using (VLifeMDS4.2). QSAR study performed on 35 analogues of which 26 were used in the training set and the rest 9 is considered for the test set. Multiple linear regression (MLR) methodology with stepwise (sw) forward- backward variable selection method was used for building the QSAR models. The results of the 2D-QSAR models were further compared with 3D-QSAR models generated by manual method. The statistical significant model (r2=0. 7782; F test=25. 735; q2=0. 5576; q2se=0. 6544; pred_r2=0. 5975; pred_r2 se=1. 0889) were developed using molecular design suite (VLifeMDS4. 2) these investigating the substitutional requirements for the favourable anti-hypertensive activity. 1FNO ligands are used for docking in auto dock software. These biological active docking compounds are used to treat hypertension.